2019
DOI: 10.1093/advances/nmz019
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Diets: Planetary Health and Its Alignment with Human Health

Abstract: To maintain planetary health, human activities must limit the use of Earth's resources within finite boundaries and avoid environmental degradation. At present, food systems account for a substantial use of natural resources and contribute considerably to climate change, degradation of land, water use, and other impacts, which in turn threaten human health through food insecurity. Additionally, current dietary patterns, rich in animal products and excessive in calories, are detrimental to both population and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 73 publications
2
93
2
10
Order By: Relevance
“…A plant-based diet is recommended by many authorities as nutritionally adequate, appropriate for all groups of people in the prevention and management of several diseases [54,55]. It has been well recognized that the occurrence of some chronic diseases among the adult population following plant-based diet is lower [11,[56][57][58]. However, some authors suggest that the existing data do not allow us to clearly evaluate the health benefits and risks of vegetarian type diets on the nutritional or health status of children and adolescents in developed countries [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…A plant-based diet is recommended by many authorities as nutritionally adequate, appropriate for all groups of people in the prevention and management of several diseases [54,55]. It has been well recognized that the occurrence of some chronic diseases among the adult population following plant-based diet is lower [11,[56][57][58]. However, some authors suggest that the existing data do not allow us to clearly evaluate the health benefits and risks of vegetarian type diets on the nutritional or health status of children and adolescents in developed countries [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Four types of modeled meat replacers, including vegetarian, vegan, insect-based, and fortification-free, were compared, and the result indicated that vegan replacers can reduce up to 87% of indictors such as climate change, land use, and fossil fuel depletion (Van Mierlo et al 2017). Fresán and Sabaté (2019) also estimated that progression from current omnivore diets to vegan and ovo-lacto vegetarian diets can achieve about 50% and 35% decrease of GHG emissions, respectively. Therefore, shifting the global food production system to more sustainable means by focusing on plant-based alternatives will help to protect limited natural resources and ensure that a sustainable environment can be maintained for human survival.…”
Section: The Environmental Concerns Of Traditional Meat Productionmentioning
confidence: 99%
“…Although replacing meat in our diet with PBMA can provide health and environmental benefits (Hallström et al, 2015;Fresán & Sabaté, 2019), the majority of consumers remain unwilling to completely transit from the consumption of meat to PBMA (Slade, 2018). Until recently, both traditional and first generation PBMA products have been mainly targeted toward vegetarians and occasional meat eaters, who do not expect similar textures and tastes to meat from plant protein alternatives.…”
Section: Consumer Attitude To Pbma: Still a Big Challengementioning
confidence: 99%
“…The negative climate impact (greenhouse gas emissions) resulting from more plant-based diets (both theoretic and real plant-based diet scenarios, i.e., self-selected diets) has been found to be ∼20-35% lower than regular diets, and ∼45-50% lower than vegan diets of the currently commonly consumed diets in high-income countries [12,13]. Variable effects on land use have been reported, e.g., a median reduction of ∼15% for diets with meat partially replaced by plant-based food [12] and a median reduction ∼50% for vegan diets [13]. On the other hand, replacing animal-based foods in the diet with plant-based foods does not always imply lower blue water use (surface and groundwater), as e.g., fruits, nuts and pulses can be more dependent on irrigation than animal foods [14].…”
Section: Introductionmentioning
confidence: 99%